The Effect of Using Epoxy As a Substitute For Hydroxyl-Terminated Polybutadiene (HTPB) on Manufacturing Solid Propellants - Maryono, Maryono; Ali, Muhammad; Lazuardi, Lazuardi (Evrimata: Journal of Mechanical Engineering, 2024)
The solid propellant consists of ammonium perchlorate (AP)/Hydroxyl- Terminated Polybutadiene (HTPB) composite material. In this research, innovation was carried out using epoxy as a substitute for HTPB. The analysis carried out in this research includes analysis of fuel propagation speed, combustion temperature, exit pressure, gas speed, and thrust force. Based on the results of research that has been carried out, increasing the addition of epoxy results in a decrease in combustion speed, combustion temperature, exit pressure, and combustion gas speed so that the resulting thrust force decreases. The most optimum composition in this research was composition A using 46% Ammonium Perchlorate, 36% Aluminum, and 18% Epoxy. The resulting thrust force on composition A is 750.5771 N. The difference in the thrust force results between HTPB and composition A is 1.8731 N. This proves that epoxy can be used as a substitute for HTPB.